2004
DOI: 10.1002/path.1667
|View full text |Cite
|
Sign up to set email alerts
|

C‐C chemokine receptor 2 (CCR2) deficiency improves bleomycin‐induced pulmonary fibrosis by attenuation of both macrophage infiltration and production of macrophage‐derived matrix metalloproteinases

Abstract: Macrophage infiltration is implicated in various types of pulmonary fibrosis. One important pathogenetic process associated with pulmonary fibrosis is injury to basement membranes by matrix metalloproteinases (MMPs) that are produced mainly by macrophages. In this study, C-C chemokine receptor 2-deficient (CCR2-/-) mice were used to explore the relationship between macrophage infiltration and MMP activity in the pathogenesis of pulmonary fibrosis, using the bleomycin-induced model of this disease process. CCR2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
114
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(132 citation statements)
references
References 47 publications
10
114
1
Order By: Relevance
“…MCP-1 has previously been reported to be a major profibrotic chemokine involved in various fibrotic processes, including recruitment of fibrocytes, induction of collagen synthesis, and up-regulation of TGF-␤1 expression in various models. 50,51,[55][56][57][58][59][60][61][63][64][65][66][67][68] Indeed, we observed that MCP-1 responses preceded the responses of fibrogenic growth factor TGF-␤1, 51,52 which were significantly higher in the lung of infected TNF Ϫ/Ϫ lungs and were well correlated with fibrotic tissue remodeling seen in TNF Ϫ/Ϫ lungs at later time points during influenza infection. Thus, depletion of MCP-1 in influenza-infected TNF Ϫ/Ϫ hosts markedly reduced lung immunopathology and tissue remodeling, and such MCP-1 depletion-improved welfare was associated with diminished production of bioactive TGF-␤1.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…MCP-1 has previously been reported to be a major profibrotic chemokine involved in various fibrotic processes, including recruitment of fibrocytes, induction of collagen synthesis, and up-regulation of TGF-␤1 expression in various models. 50,51,[55][56][57][58][59][60][61][63][64][65][66][67][68] Indeed, we observed that MCP-1 responses preceded the responses of fibrogenic growth factor TGF-␤1, 51,52 which were significantly higher in the lung of infected TNF Ϫ/Ϫ lungs and were well correlated with fibrotic tissue remodeling seen in TNF Ϫ/Ϫ lungs at later time points during influenza infection. Thus, depletion of MCP-1 in influenza-infected TNF Ϫ/Ϫ hosts markedly reduced lung immunopathology and tissue remodeling, and such MCP-1 depletion-improved welfare was associated with diminished production of bioactive TGF-␤1.…”
Section: Discussionmentioning
confidence: 83%
“…51,[62][63][64][65][66][67][68] Thus, given the dysregulated MCP-1 and its association with heightened TGF-␤1 production seen in influenza-infected TNF Ϫ/Ϫ lungs (Figure 7), we further investigated the role of MCP-1 in heightened immunopathology and fibrotic reaction in the lung of TNF Ϫ/Ϫ mice by means of MCP-1 depletion. To this end, MCP-1 anti-serum (anti-MCP-1) or the control serum was administered intraperitoneally to TNF Ϫ/Ϫ mice on days 2, 5, and 9 following influenza infection, and the mice were sacrificed at day 21 after infection for morphometric quantification of lung immunopathology and fibrotic remodeling ( Figure 8A).…”
Section: Attenuation Of Lung Immunopathology In Influenza-infected Tnmentioning
confidence: 99%
“…MCP-1 may also promote the fibrotic phenotype. For instance, mice lacking CCR2 or overexpressing mutant MCP-1 are protected against bleomycin-induced lung fibrosis (28,29). Intriguingly, elevated levels of MCP-1 have been detected in lavage fluid obtained from children with interstitial lung disease (44).…”
Section: Discussionmentioning
confidence: 98%
“…Although MCP-1 is chemotactic for monocytes and macrophages, studies have led to an appreciation that it also promotes fibrosis in response to bleomycin (28,29) and affects the inflammatory response to influenza A virus infection (26). To determine whether elevated levels of MCP-1 were associated with fibrosis, lung histology was investigated during infection.…”
Section: Neonatal Hyperoxia Promotes Fibrosis In Infected Adult Micementioning
confidence: 99%
“…However, in a model of bleomycin-induced pulmonary fibrosis, it was suggested that MCP-1 might regulate MMP-9 expression; however, no direct evidence was provided. 33 In addition, reduced expression of MMP-9 in MCP-1-null macrophages can be restored by addition of TNF-␣, an acute-phase proinflammatory cytokine with a role in the foreign body response that has received little attention. 6,34 TNF-␣ also induces apoptosis in macrophages adherent to biomaterials, and IL-4 inhibits the apoptosisinducing abilities of TNF-␣.…”
Section: Discussionmentioning
confidence: 99%